Muscle Mass and Muscle Strength Following 6 Weeks of Blood Flow Restriction Combined with Low-Intensity Strength Training in Overweight Adolescents - Soontaraporn Huntula; Wattana Nuttouch (OVS LLC, 2023)
Background and Study purpose. Blood flow restriction training is a new training technique that involves low-intensity exercise and can generate physiological changes equivalent to high-intensity exercise. The aim of this study is to assess the impact of blood flow restriction in conjunction with low-intensity resistance exercise on muscle mass and muscle strength among overweight adolescents, in comparison to conventional resistance exercise. Materials and methods. The study involved two randomized groups: an experimental group, which performed 40% of one repetition maximum (1RM) resistance exercise combined with 60% of arterial occlusion pressure (AOP), and a traditional resistance exercise group, which performed 70% of 1RM resistance exercise. All participants underwent pre-test and post-test evaluations for body composition, 1RM, and muscle circumference. The training program lasted for six weeks and consisted of upper and lower body training, including exercises such as leg press, leg curl, arm curl, and arm extension. Results. The group that underwent low-load blood flow restriction (LLBFR) training showed a notable increase in muscle mass (p<0.049) as well as arm and leg circumference (p<0.047 and p<0.046, respectively) compared to before the training program, similar to the results of high-intensity resistance exercise. Conclusions. Combining blood flow restriction with low-intensity resistance training is a potentially effective approach to increase muscle size and strength, especially in overweight adolescents. Moreover, this type of training can decrease the amount of exercise load, making it a feasible option for individuals who may not tolerate high loads due to certain medical conditions or other limitations.